Manual Educativo Sobre Cuidados Com Gastrostomia Em Crianças - Sales, Priscila Nunes Da Cruz [UNIFESP] (2018)
Introduction: Gastrostomy is a procedure in which a catheter is inserted into the stomach through an opening in the anterior abdominal wall. In the literature, there is a shortage of studies focused on the implications of using gastrostomy for family members and caregivers. Objective: To develop and to validate an educational manual on gastrostomy care in children, for parents and caregivers. Method: A bibliographic survey was carried out to construct the contents of the manual and to validate it with specialists and parents and / or caregivers of children with gastrostomy. For the validation with specialists, the Delphi technique was used, sending questionnaires to evaluate the content and appearance of the manual. Validation with parents and caregivers of children with gastrostomies was done using a Likert scale with questions in simple language to evaluate the comprehension of content and illustrations. Results: The elaboration of the manual has been validated by experts in two rounds of Delphi technique, the percentage of absolute agreement of all manual value reached 97.91%, with 7 out of 8 questions presented 100% agreement. Validation with target audiences showed a 100% agreement rate, all participants scored 3 on the Likert scale for all questions. The "Manual of Care of the Child with Gastrostomy", has 21 pages, 8 chapters and 38 figures, of simple language content for better understanding of the target audience that is intended to reach, with registration in ISBN for printed paper. Conclusion: Developed and validated the educational manual on gastrostomy care in children, for parents and caregivers.